Does uncertainty affect real activity? Evidence from state-level data - Haroon Mumtaz (Queen Mary University of London, School of Economics and Finance, 2018)
We use variation in the effect of US-wide or global uncertainty on state-level uncertainty to identify the impact of this shock on real activity. We ?nd that increases in uncertainty do have an adverse impact on real income, employment and unemployment. Thus, uncertainty shocks can be a source of economic fluctuations.
Keywords: C15; C32; E32; 330; Uncertainty shocks; Instrumental variables; US states